Shaping Tomorrow's Educators Through Service-Learning: The Emergence of Critical Global Citizenship in Pre-Service Teachers - Adarlo, Genejane M (Archīum Ateneo, 2024)
Teacher preparation is salient in the emerging professional identity of pre-service teachers. This preparation involves integrating meaningful and relevant experiences into the curriculum, which would allow pre- service teachers to put their emerging teacher identities into practice. Among pedagogical approaches in teacher education, service-learning can provide meaningful and relevant experiences in preparing pre-service teachers for the teaching profession. This chapter explores the transformative influence of service-learning on pre-service teachers' sense of self in relation to their chosen profession. Drawing on the lived experiences of eight pre-service teachers in teaching literacy and value formation for their community engagement in service-learning, critical global citizenship was found to be an integral part of their emerging teacher identity. Specifically, engaging in service-learning helped them find a deeper sense of purpose in their future professions as educators. This deeper sense of purpose stems from their understanding of the broader social, economic, and political contexts in which education takes place. These pre-service teachers, in turn, were able to recognize their roles as educators not only within the classroom but also as agents of change in the larger community. These findings offer valuable insights into the transformative potential of service-learning in shaping tomorrow's educators whose sense of self is committed to promoting equity and social justice.